Prasangka, Politik, and Islamofobia: Bagaimana Kebencian Membentuk Ulang Masyarakat Demokratis - Sumant Kumar (Badan Strategi Kebijakan Hukum, 2025)
In the past few years, there has been an extensive rise in Islamophobia-related cases in Western democratic countries. This study, through the lens of prejudice theory, explores the factors that have increased pervasive hatred toward Muslim community, due to social fragmentation, political polarization and hate-motivated speeches initiated by the political parties and state. The hatred in a democratic society is the result of political narratives which later reshaping policy to target Muslim minority. The research aims to analyze and examine how deep-rooted bias against the Muslim communities through institutional, ideological and political hatreds continues shaping public, state, and media perception to discriminate from the main society. This study has applied qualitative content analysis to understand the increasing pattern of hate-motivated crimes. The objective behind the study is to trace historical and present narratives through hate speeches that fuel anti-Muslim sentiment, including how terrorism is linked with security threat, which reinforce prejudice against the Muslim community. This study, with the help of prejudice approach, explains that what are the factors and circumstances that make political parties and the state to increase their hatred towards the Muslim community through hate speeches which promote islamophobia in society. The findings of this study explore that the hatred through political speeches not only fragmented the Muslim minority from the mainstream society but also discriminatory changes in the policy, legitimizing the activity. The hatred in the democratic countries has increased criminal activities, surveillance, exclusion from society, and institutional biases.